Process development for an inducible rituximab‐expressing Chinese hamster ovary cell line. (30th November 2018) - Mellahi, Kahina; Cambay, Florian; Brochu, Denis; Gilbert, Michel; Perrier, Michel; Ansorge, Sven; Durocher, Yves; Henry, Olivier
Abstract : Inducible mammalian expression systems are becoming increasingly available and are not only useful for the production of cytotoxic/cytostatic products, but also confer the unique ability to uncouple the growth and production phases. In this work, we have specifically investigated how the cell culture state at the time of induction influences the cumate‐inducible expression of recombinant rituximab by a GS‐CHO cell line. To this end, cells grown in batch and fed‐batch cultures were induced at increasing cell densities (1 to 10 × 10 6 cells/mL). In batch, the cell specific productivity and the product yield were found to reduce with increasing cell density at induction. A dynamic feeding strategy using a concentrated nutrient solution applied prior and postinduction allowed to significantly increase the integral of viable cells and led to a 3‐fold increase in the volumetric productivity (1.2 g/L). The highest product yields were achieved for intermediate cell densities at induction, as cultures induced during the late exponential phase (10 × 10 6 cells/mL) were associated with a shortened production phase. The final glycosylation patterns remained however similar, irrespective of the cell density at induction. The kinetics of growth and production in a 2 L bioreactor were largely comparable to shake flasks for a similar cell density at induction. The degree of galactosylation was found to decrease over time, but the final glycan distribution at harvest was consistent to that of the shake flasks cultures. Taken together, our results provide useful insights for the rational development of fed‐batch cell culture processes involving inducible CHO cells. © 2018 American Institute of Chemical Engineers Biotechnol. Prog ., 35: e2742, 2019